Comparative Efficacy of Acupuncture-Related Techniques for Urinary Retention After a Spinal Cord Injury: A Bayesian Network Meta-Analysis - He, Kelin; Li, Xinyun; Qiu, Bei; Jin, Linzhen; Ma, Ruijie (Frontiers in Neurology, 2022)
Background Urinary retention is one of the most frequent complications of spinal cord injuries (SCI) and negatively impacts patient satisfaction and quality of life. Acupuncture as an integral part of traditional Chinese medicine (TCM) has recently drawn widespread attention for its potential in the management of urinary retention. However, there are many different styles of acupuncture-related techniques, and the optimal choice of acupuncture for urinary retention after SCI is still unclear. Hence, this study uses a Bayesian network meta-analysis (NMA) to compare the efficacy of different types of acupuncture therapies using both direct and indirect evidence. Methods Randomized controlled trials of acupuncture-related techniques for treating urinary retention after SCI were retrieved from the following electronic databases: Pubmed, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), the Chinese Biomedical Literature Service System (SinoMed), the Wan-Fang database, and the Chinese Scientific Journals Database (VIP). The retrieval time was from inception to November 2020. Clinical effective rate (CER) was the primary outcome indicator and residual urine volume (RUV) was the secondary outcome indicator. A Bayesian NMA was performed using the Markov chain Monte Carlo method in R software (version 3.6.1) interfacing with JAGS software (version 4.3.0). The node-splitting method was used to identify inconsistencies. In addition, a comparative adjusted funnel plot was used to assess publication bias. Results A total of 26 randomized controlled trials involving 1,652 patients were included. Bayesian NMA showed that electroacupuncture combined with moxibustion ranks first in both CER and RUV. In addition, in terms of cumulative probability, electro-acupuncture combined with moxibustion ranked first in CER. The results of the node splitting method revealed that direct and indirect evidence were consistent (P > 0.05). In addition, publication bias was detected. Conclusion A Bayesian NMA that combined direct and indirect comparisons showed that electro-acupuncture combined with moxibustion had a better effect on urinary retention due to SCI. However, it still needs a large sample size and high-quality randomized controlled trials to verify this finding. Systematic Review Registration:https://inplasy.com/, identifier: INPLASY2021110005.